2014
DOI: 10.1063/1.4871719
|View full text |Cite
|
Sign up to set email alerts
|

Skin explosion of double-layer conductors in fast-rising high magnetic fields

Abstract: Articles you may be interested inDesign of pulsed guiding magnetic field for high power microwave generators Rev. Sci. Instrum. 85, 094703 (2014); 10.1063/1.4894204 Fast modeling of flux trapping cascaded explosively driven magnetic flux compression generators Rev. Sci. Instrum. 84, 014703 (2013); 10.1063/1.4775488Electrical explosion of metals in fast-rising megagauss magnetic fields An experiment has been performed to study the electrical explosion of thick cylindrical conductors using the MIG pulsed power g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(6 citation statements)
references
References 30 publications
2
4
0
Order By: Relevance
“…The temperature range where all of the spectral features could have been observed simultaneously was 2-2.5 eV. This is consistent with previous electrode-plasma temperature estimates at these linear current densities (0.1-1 MA=cm) [57][58][59].…”
Section: B Density and Temperaturesupporting
confidence: 91%
“…The temperature range where all of the spectral features could have been observed simultaneously was 2-2.5 eV. This is consistent with previous electrode-plasma temperature estimates at these linear current densities (0.1-1 MA=cm) [57][58][59].…”
Section: B Density and Temperaturesupporting
confidence: 91%
“…As the rate of rise of the magnetic field is increased, the magnetic induction, responsible for the formation of plasma, increases and tends to the value found in the plane geometry. The simulation results agree well with the experimental data [4,15,16], suggesting an adequacy of the used model.…”
Section: Simulation Results and Comparison With Experimental Datasupporting
confidence: 79%
“…[2][3][4][5][6][7] It was shown that depending on the current density, different modes of wire explosions can be obtained, i.e., "slow" explosion (j 10 7 A/cm 2 ) when magneto-hydrodynamic (MHD) instabilities have enough time to develop or, for significantly larger current densities, "fast" explosions, characterized by the development of thermal instabilities. [8][9][10][11][12] For fast explosions, if the skin time is significantly shorter than the current rise time, the explosion can be considered volumetric. On the other hand, an explosion is considered "superfast," when the skin-layer thickness is much smaller than the wire radius.…”
Section: Introductionmentioning
confidence: 99%